The Concept of «Rules-Based Order» as applied to Outer Space - I. Yu. Shtodina (Московский журнал международного права, 2025)
INTRODUCTION. In contemporary international law, the idea of replacing the existing principles of international law, primarily enshrined in the UN Charter, with a “rules-based order” has gained popularity. The very use of this term is strongly criticized in the international community due to the impossibility to establish the content of this term, its legal basis and the possibility of its change. However, with regard to international space law (ISL), the application of the “rulesbased order” is often attempted to be presented as an opportunity to supplement the legal gaps in international space law with the provisions of the said “legal order”.MATERIALS AND METHODS. The article analyses both the doctrinal understanding of the content of the term “rules-based order” and its applicability to the creation of new sources of international space law, revision and supplementation of existing legal norms. The subject of the analysis is the materials of the foreign legal press, articles in legal journals and the Internet. In addition to the data of the science of international law, the scientific categories of philosophy, political science and economics are also used. Historical, formal-legal, comparative-legal method and the method of system analysis, etc. were used in the study.THE RESEARCH RESULTS. The successful development of international space law and the harmonization of its existing norms with the requirements of the time depends, first of all, on the common desire of participants in the exploration and use of outer space to update the entire existing legal “framework” of the existing norms of the ISL. Such updating is possible both through the elaboration of new universal treaties in this area of international relations and through the adoption of soft law norms, which, if universally recognized and approved, could eventually become universal norms of the ISL. Rejection of already existing treaties, primarily the 1967 Treaty, is unlikely to contribute to preserving and strengthening the existing legal order in outer space. Moreover, the established legal order in space exploration and use should not and cannot be replaced by vague legal ideas reflecting the position of a minority of states.DISCUSSION AND CONCLUSIONS. The study substantiates the conclusion that attempts to replace peremptory norms of international law with the provisions of “rules-based order” are, in fact, doomed to failure. First of all, because the legal content of the mentioned term and the possibility of changing the provisions constituting this legal order are not clear. In addition, only the adoption of general universal norms in the field of international law can serve as a guarantee of stability and ensuring equal interests of the participants in international relations. In the field of the ISL, attempts to fill the legal gaps created by the application of the provisions of the “rules-based order” are all the more unpromising, since, in fact, they create unilateral advantages for countries that have already been actively and for a considerable period of time developing outer space. Attempts to replace or broadly interpret the norms of the current ISL undermine the existing legal order in outer space. Replacing universal norms in the field of space exploration and use with national legislation and regional acts cannot solve the problems created in space legislation, although recommendations of international intergovernmental organizations and guidelines can serve as examples of soft law norms that can eventually become norms of the ISL. The main task is to preserve and strengthen the legal order that has been created and has been in force in space law for decades. New technical achievements, expansion of the range of participants in space activities, and environmental problems put new legal tasks on the agenda, but their solution is possible only with equal consideration of the interests of all participants in space legal relations.